Growth and production of monosex tilapia (Oreochromis niloticus L.) under different levels of stocking densities: Monosex tilapia growth and production under different stocking - Sapkota, Karuna; Chaudhary, Susant Mani; Bhandari, Laxmee; Magar, Mahesh Budha; Chaudhary, Birendra; Jha, Subhash Kumar; Pandey, Prabin; Shrestha, Jiban (SAARC Journal of Agriculture, 2022)
Monosex tilapia (Oreochromis niloticus L.) was evaluated in a freshwater pond for 100 days at Gokuleshwor, Baitadi, Nepal during the summer and rainy seasons of 2019. Fingerlings were supplied at stocking densities of 5, 10, 15, and 20 fish per m3. At the time of stocking, the average fingerling weight was 8.5 grams. Each treatment had four replicates. Each of the treatments involved feeding the fish twice a day. The results revealed that the specific growth rate and survival rates decreased with increasing levels of stocking density. As stocking density increased, the growth performance of tilapia dropped. Fish growth was the highest at a stocking density of 5 fish per m3, but the production was the highest at a stocking density of 20 fish per m3. According to the findings of this study, farmers should use higher stocking densities to maximize production. SAARC J. Agric., 20(2): 247-259 (2022)